2004
DOI: 10.1162/15353500200404115
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Force Assisted Targeting Facilitates Ultrasonic Molecular Imaging

Abstract: Ultrasonic molecular imaging employs contrast agents, such as microbubbles, nanoparticles, or liposomes, coated with ligands specific for receptors expressed on cells at sites of angiogenesis, inflammation, or thrombus. Concentration of these highly echogenic contrast agents at a target site enhances the ultrasound signal received from that site, promoting ultrasonic detection and analysis of disease states. In this article, we show that acoustic radiation force can be used to displace targeted contrast agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 27 publications
1
68
0
Order By: Relevance
“…Current FDA-approved microbubble contrast agents are based on a lipid monolayer or albumin shell encapsulating a high-molecular weight gas [6][7][8]. The gas core provides the acoustic impedance mismatch which makes microbubbles highly echogenic and allows the microbubbles to be manipulated with acoustic radiation force [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current FDA-approved microbubble contrast agents are based on a lipid monolayer or albumin shell encapsulating a high-molecular weight gas [6][7][8]. The gas core provides the acoustic impedance mismatch which makes microbubbles highly echogenic and allows the microbubbles to be manipulated with acoustic radiation force [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Since spatial localization with ultrasound radiation force permits higher vehicle delivery rates than can be achieved by flow/adhesion dynamics alone, it is desirable to produce a drug-carrier vehicle which retains the capability to be acoustically concentrated [4,10,11,28]. Taking advantage of the acoustic properties of lipid-coated microbubbles and the fusogenicity of liposomes motivated us to create a new drug delivery vehicle by mounting the liposomes on microbubble shells.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity to impart kinetic energy to gas-filled microbubbles by ultrasound has been previously characterized by Dayton et al, 8,9 and has been employed to modulate microbubble adhesion to endothelial epitopes for molecular imaging, 11,12 or to deliver a cytotoxic drug to tumor cells. 13 The radiation force on a given microbubble is maximal when the incident ultrasound is at the natural resonance frequency of the microbubble.…”
Section: Discussionmentioning
confidence: 99%
“…For the lipid-shelled microbubbles used in this study, the average resonance frequency is close to 2.2 MHz. 9,11 The intravascular ultrasound catheter used in our in vivo studies is FDAapproved to facilitate thrombolysis for treatment of stroke. Importantly, no major direct detrimental biological effects to the vessel wall were observed with this type catheter delivering the same amount of energy as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated an over 100-fold increase of microbubble adhesion due to ARF usage [58], [59]. Additionally, the image signal-to-noise ratio increased significantly due to the application of ARF [60]. In vivo validations have verified that the application of ARF enhanced the detection sensitivity and diagnostic utility of ultrasound molecular imaging [62], [63].…”
Section: Assistance Of Acoustic Radiation Force (Arf)mentioning
confidence: 93%